BATTERED WOMAN SYNDROME SEBAGAI PENYEBAB TERJADINYA SUATU TINDAK PIDANA OLEH WANITA DALAM LINGKUNGANNYA. - Nurijlal Hafizh Syah (Fakultas Hukum Universitas Tarumanagara, 2021)
Battered Woman Syndrome (BWS) is a symptom of a syndrome that causes changes in a woman's personality and behavior as a result of the events and acts of violence that she receives in life, so that it makes the individual potential to commit a criminal act that has not been done by the person in his life. As a result of the changes that occur in his personality and behavior, a new personality is created that leads her to perform some actions that go beyond the habits of a woman throughout her life, they can be murder, mutilating, burning alive someone and others. This incident is commonly experienced by women who have problems of violence in romantic or domestic relationships and do not get protection and attention in the midst of their living environment so that a review is needed that discusses the responsibility of the perpetrator in accountability for her criminal acts before the law.